A herpesvirus saimiri protein required for interleukin-2 independence is associated with membranes of transformed T cells. - Lund, T (1995)
A region of the herpesvirus saimiri genome encoding an mRNA with two open reading frames (ORFs) has been identified to be essential for transformation of T cells. Deletion of either ORF resulted in the loss of transforming ability. ORF-1 has been shown to code for a collagen-like oncoprotein. This study shows for the first time that the bicistronic mRNA can translate a 32-kDa protein from ORF-2. Polyclonal serum to ORF-2 was generated by using a glutathione fusion protein. Using this antiserum, ORF-2 was localized in cell membranes and is expressed on the outer cell membrane. The half-life of this membrane protein was found to be about 5.5 h. Limited sequence similarity was found between ORF-2 and interleukin-11; however, no secretion of ORF-2 protein was detected in supernatants from transformed cells. Further studies are required to investigate the potential interaction with the interleukin-11 receptor.